A preliminary survey: Problems of physical and chemical properties of community consumption water quality - Kownarumit, Supaporn; Chuasuwan, Aungsana; Ratchathumma, Phitchayapa; Poolkasem, Angwara (Bulletin of Applied Sciences, 2022)
Problems of physical and chemical quality of consumption water in requested communities in Thailand were a preliminary survey. The consumption water samples of the communities in Phrae, Nong Bua Lam Phu, Nakhon Phanom, Bungkarn and Songkha province were collected for testing the physical and chemical properties (26 items) of the water according to Thai drinking water standards: Notification No. 61 (2524) and No. 135 (2534). The standards were approved by the Food and Drug Administration (FDA), used as the regulation for bottled drinking water that is available in Thailand. The purpose of the survey was to explore the quality problems of raw water (well water, deep well water, shallow well water and river water), also the tap water from both groundwater and deep well water. The obtained information will be used as guidance for improvement of the water quality to meet the standard of consumption water, as well as for choosing a proper drinking water filter system to fit the existing water source quality. Results showed that all the bottled drinking water and rain water consuming in the community daily lives were met the quality standards. Most of the tap water, and raw water did not meet the drinking water standard; however, these types of water were not consumed directly. The problems of community consumption water quality found in this survey comprised 14 items, namely color, odor, turbidity, pH, total solids, total hardness, sulfate, chloride, barium, nitrate, iron, manganese, aluminium and silver.concerned with comparison of the estimation of measurement uncertainty of determination of mercury in drinking water by using ISO/GUM approach and method validation approach. There were many sources of uncertainties when using ISO/GUM approach such as precision, volumes of samples, volumes of blank and concentration of samples. Meanwhile method validation approach had only precision and bias. It was found that the expanded uncertainties were 8.5 % and 11%, respectively. The estimation of measurement uncertainty in this paper can be applied to other measurement methods that using calibration curves.